Efektivitas Bimbingan Kelompok Teknik Problem Solving untuk Meningkatkan Self-Awareness pada Siswa Mts Muhammadiyah Karangkajen - Corry Ardana; Aprilia Setyowati; Amien Wahyudi; Rohmatus Naini (Indonesian Journal of Educational Counseling, 2026)
The Effectiveness of Group Guidance Using the Problem-Solving Technique is closely connected to adolescent development, particularly in understanding themselves, regulating emotions, and building healthy social interactions. Initial observations at MTs Muhammadiyah Karangkajen showed that some students struggled to recognize their feelings, strengths, and weaknesses, and understand the impact of their behavior on others. This study examined the effectiveness of this technique in improving students’ self-awareness. Using a quantitative pre-experimental one-group pretest–posttest design, 101 seventh-grade students with low self-awareness scores were selected through purposive sampling. The Self-Awareness Scale was administered before and after the intervention, and data were analyzed using SPSS with normality testing and paired sample t-tests. Results indicated a significant increase in self-awareness, demonstrating the technique’s effectiveness in supporting students’ emotional and social development.. KEYWORDS: Group Guidance, Problem Solving, Self-Awareness, Students